Effect of exogenous enzymes on ruminal fermentation, pelletability and palatability of blueberry products in equine feed, and the effects of quantity of protein and starch on equine cecal environment - Sandwick, Michael (Kansas State University, 2022)
Enhancing ruminal fermentation of feed is an important consideration for producers of beef and dairy cattle. One method for enhancing fermentation of fiber is application of exogenous fibrolytic enzymes (EFE) to feed. To determine whether method used to apply EFE impacts fermentation parameters by bovine ruminal microorganisms, 3 methods of applying Vista Pre-T (AB Vista, Inc., Plantation, FL.) on a total mixed ration (TMR) were evaluated: sprayed liquid enzyme (wet), liquid enzyme combined with molasses (molasses) prior to mixing molasses into TMR, and dried enzyme added to vitamin and mineral premix (dry) prior to mixing vitamin and mineral premix into TMR. Five grams (dry matter; DM) treated TMR, which were calculated to contain 4.82 mg (DM) Vista Pre-T, were placed into fermentation bottles. Additionally, there also were cultures that received 5 g (DM) untreated TMR with 2.41 mg (DM) liquid Vista Pre-T dosed directly (direct-dosed) into fermentation bottles at the time of inoculation. Negative control cultures contained 5 g (DM) untreated TMR and were not exposed to EFE. One hundred twenty-five milliliters McDougall’s buffer and 25 mL ruminal fluid, which served as inoculum, were combined with TMR in fermentation bottles. Bottles were sparged with N₂, fitted with gas pressure monitoring modules, and incubated for 48 h at 39°C. Molasses enzyme application reduced maximum rate of gas production and increased time to reach half maximum gas production compared to all other applications (P ≤ 0.05). Wet application led to greater terminal pH compared to all other treatments (P ≤ 0.05). Cultures containing molasses treatment had greater (P ≤ 0.02) terminal pH compared to dry and direct-dosed treatments. Concentrations of total VFA, acetate, propionate, isobutyrate, and isovalerate were not affected (P ≥ 0.12) by application method. Acetate:propionate ratio was increased when cultures contained molasses treatment compared to direct-dosed and negative control cultures (P ≤ 0.01). Butyrate concentrations were greater when cultures contained molasses compared to all treatments (P ≤ 0.009) except dry (P = 0.07). Molasses and dry application methods resulted in greater valerate concentrations (P ≤ 0.03) compared to cultures containing wet treatment. Dry application led to greater caproate concentrations compared to all treatments (P ≤ 0.02) except molasses (P = 0.40). In vitro dry matter disappearance (IVDMD) was greater for cultures containing dry and molasses treatments than all other application methods (P ≤ 0.0009). Neutral detergent fiber disappearance (NDFD) was greatest for cultures containing dry application (P < 0.0001) with wet application method yielding the lowest NDFD (P < 0.0001); however, ranges observed for all parameters were small. While molasses treatment had the greatest impact on dry matter disappearance in vitro, this effect has not been confirmed in vivo. The objective of this study was to evaluate the impact of liquid blueberry juice (BJ65) or blueberry puree (BP30) used as a binding agent on pellet durability and palatability of a typical equine concentrate when included at 4% of the pellet. Molasses was used as a control. Production data, pellet durability, and moisture content were evaluated in 1 replicate for each treatment. Because moisture content of condition mashes was 17.59% and 18.11% for BJ65 and BP30 treatments, respectively, greater inclusion of blueberry product would likely cause roller slippage and complicate the pelleting process due to increased liquid. Pellet durability met industry standards for all treatments. Pellets were fed in a 3-period crossover study to 9 two-year-old horses to determine the effect of blueberry products on acceptability. All animals were allowed 10 min to consume 1.36 kg at 0700 h and 1700 h each day for 3 d. Consumption time and amount consumed were recorded to calculate intake, intake rate, and intake ratio (IR). No horses consumed all pellets within the allotted time, and thus, treatment differences for intake and intake rate were the same. Period tended to impact intake (P = 0.0909), with horses consuming less during period 1 than period 3 (P = 0.0317), but period had no effect (P = 0.2881) on IR. Treatment influenced intake (P < 0.0001), with decreased intake of BP30 compared to control and BJ65 (P ≤ 0.0001). Intake ratio was greater (P = 0.0075) for BJ65 than BP30 with IR of 0.5069 and 0.4227, respectively. Because IR of 0.50 indicates equal consumption of treatment pellets compared to control, consumption of BJ65 was no different than control. Thus, BJ65 appears to be more acceptable to horses than BP30 when included in dietary pellets at this rate. Fluctuations in relative abundances of microorganisms in the equine hindgut have been associated with colic, and, while equine diets contain varying ratios of forage:concentrate, little is known regarding effects of increasing dietary starch on the microbiome of the equine hindgut. Thus, an experiment was conducted with six cecally cannulated horses (524 ± 65.5 kg BW) to evaluate effects of increasing dietary starch on equine cecal microbiota. Starch was supplied via pelleted corn and increased by 0.5 g starch·kg BW⁻¹·meal⁻¹ every 7 d until horses received 3.5 g starch·kg BW⁻¹·meal⁻¹. Smooth bromegrass hay and water were offered ad libitum. Meals were fed every 6 h, starting at 0600 h. On d 7 of each period, cecal digesta were collected every 2 h for 12 h, with the h 0 collection occurring prior to the 0600 h feeding. Cecal samples obtained from all time points for a given level of dietary starch within an individual horse were pooled, DNA was extracted for PCR amplification of the 16S rRNA gene (V3 and V4 regions), and sequencing was performed using an Illumina MiSeq. Mothur was utilized for clustering of features and operational taxonomical units (OTUs), and sequences were submitted to SILVA database for identification. Data were analyzed (SAS version 9.4) as a completely randomized design with fixed effect of treatment (g starch·kg BW⁻¹·meal⁻¹) and random effect of horse. Across treatments, Firmicutes was the most abundant phylum, followed by Bacteroidota. Feeding 1.5 g starch·kg BW⁻¹·meal⁻¹ elicited the greatest changes in microbiota, indicated by decreased (P ≤ 0.0469) relative abundances (RA) of Rikenellaceae, Prevotellaceae, RF16 group, Spirochaetaceae, Alloprevotella, Prevotella UCG-003, Prevotella UCG-004, RF16 group genus, and Treponema compared to all other treatments. Conversely, feeding 1.5 g starch·kg BW⁻¹·meal⁻¹ resulted in increased (P ≤ 0.0045) RA of Christensenellaceae and the R-7 group genus compared to all other treatments. If a horse presented with symptoms of colic, it was removed from the experiment. Data obtained when feeding 0.5, 1.0, and 1.5 g starch·kg BW⁻¹·meal⁻¹ were compared between horses that completed the trial and those removed using a covariate of 0 g starch·kg BW⁻¹·meal⁻¹. When consuming 0 g starch·kg BW⁻¹·meal⁻¹, horses that persisted had greater (P ≤ 0.00454) RA of Aeromonadales, Succinivibrionaceae, and Selenomonadaceae compared to horses that were removed. When feeding 0.5 g starch·kg BW⁻¹·meal⁻¹, no differences in RA of taxa were detected between horses that persisted and horses that would later be removed. Horses that were removed had greater RA of Colidextribacter (P = 0.0057) compared to horses that persisted when feeding 1.0 g starch·kg BW⁻¹·meal⁻¹. When consuming 1.5 g starch·kg BW⁻¹·meal⁻¹, horses that persisted had greater (P ≤ 0.0500) RA of Negativicutes, Acidaminococcales, Acidaminococcaceae, Phascolarctobacterium, and Ruminococcus compared to horses that were removed. This is one of the first reports describing effects of gradually increasing dietary starch on equine cecal microbiota in vivo. As well, this is the first report to compare cecal microbiota of horses tolerant of increasing dietary starch to those susceptible to colic in response to such dietary challenge. Dietary protein recommendations for equines are not consistent and may not account for microbial nitrogen requirements in the equine hindgut. To assess the impact of nitrogen on fermentation by equine cecal microorganisms, cecal fluid from 4 cecally cannulated horses was used to inoculate fermentation bottles containing buffer, forage, and supplemental nitrogen. In experiment 1, sodium caseinate (SC) provided 0, 0.5, 1, 2, or 4% additional CP to bottles containing alfalfa (22.4% CP) or native warm season prairie grass hay (4.8% CP). Bottles were equipped with continuous gas pressure monitors and placed into a shaking incubator for 48 h at 39°C. Cultures with alfalfa had greater (P < 0.0001) in vitro dry matter disappearance (IVDMD), NDF disappearance (NDFD), ADF disappearance (ADFD), cumulative gas production and total VFA than those with grass hay. All levels of sodium caseinate increased gas production (P ≤ 0.05) and decreased pH (P < 0.003) in cultures with grass hay. Sodium caseinate at 1, 2, or 4% additional CP increased IVDMD, NDFD, and ADFD (P < 0.01), while 4% additional CP also increased total VFA (P < 0.01) in cultures with grass hay. For experiment 2, SC, fishmeal, soybean meal (SBM), whey, porcine blood plasma, and L-lysine hydrochloride were added to supply 2% additional CP equivalent to cultures with grass hay. All nitrogen sources decreased pH and increased IVDMD, NDFD and ADFD (P ≤ 0.01), with the largest effects elicited by SC, L-lysine, and whey (P ≤ 0.05). Total VFA (P ≤ 0.04) and gas (P ≤ 0.05) production increased with L-lysine, whey, SC, SBM, and fishmeal. While nitrogen supplementation had minimal effects on cultures containing alfalfa, it altered fermentation and increased digestibility, as measured by IVDMD, NDFD, and ADFD, of grass hay, more notably with more soluble protein sources.
Keywords: Equine; Microorganisms; Protein; Starch; Fermentation; Enzymes